Migrant physicians' choice of employment and the medical specialty general practice: a mixed-methods study - Linda Sturesson; Per J. Palmgren; Magnus Öhlander; Gunnar H. Nilsson; Terese Stenfors (BMC, 2021)
Abstract Objective In many countries, migrant physicians (MP) tend to fill staff shortages in medical specialties perceived as low status. The aim of this study was to explore aspects that influence MPs', with a medical degree from outside EU/EEA, choice of employment and medical specialty in Sweden, and to explore and understand a potential over-representation in general practice (family medicine), a specialty suffering from staff shortages in Sweden. Methods A mixed-methods approach was applied. This included questionnaire data from 101 MPs training and working as medical specialists in Sweden and semi-structured interview data from four MPs specializing in general practice. Results Regardless of specialty, the most influential aspects when choosing employment were the ability to combine work with family, to develop one´s competence, and to have highly competent colleagues. Women scored higher on some aspects related to private life and the surroundings. More than half (55%) of the respondents specialized in general practice, and more women than men. The MPs in general practice scored higher on the aspect 'ability to have the same patients for a longer period' than MPs specializing in other specialties. No significant difference between MP general practitioner respondents and MPs in other medical specialties was found in relation to the item 'Was the specialty your first choice?ʼ. Aspects identified in the interviews that influenced the choice to specialize in general practice related to job opportunities, positive experiences of primary health care, working conditions, and family conditions. Conclusion Labour market conditions such as high competition, and the time-consuming recertification process, can influence the choice to specialize in general practice as this reduces the time to become a medical specialist. We however did not find any results indicating that MPs' decision to specialize in general practice and to work as general practitioners was any less voluntary than that of MPs who chose other specialties.